Electrochemical‐ and Fluorescent‐Mediated Signal Amplifications for Rapid Detection of Low‐Abundance Circulating Tumor Cells on a Paper‐Based Microfluidic Immunodevice. Issue 4 (21st January 2014) - Wu, Yafeng; Xue, Peng; Hui, Kam M.; Kang, Yuejun
Abstract The design of a novel paper‐based microfluidic immunodevice with combined electrochemical‐ and fluorescent‐mediated signal amplifications for the highly specific and ultrasensitive point‐of‐care detection of rare circulating tumor cells is reported.